Buddhism in South-East Asia : a cultural survey - Ahir, D. C. (Delhi : Sri Satguru Publications, 2001)
Contributed articles.
PS Intra Bakti / Hayatul Azlah
Includes bibliographical references.
Keywords: Buddhism -- Southeast Asia -- History; Southeast Asia -- Civilization